Marketing Management in Islamic Boarding Schools: Integrating Promotion Mix and Faith-Based Values for Sustainable Student Recruitment - Riema Afriani Kusumadewi; Badrud Tamam; Aminudin Aminudin; Ahmad Farihin; Ahmad Ramdhan (MASI Mandiri Edukasi, 2026)
Islamic boarding schools (pesantren) currently face social, economic, and digital pressures that force them to reimagine how they communicate the value of education to the community. This study aims to explore the implementation of promotional mix strategies in Islamic boarding schools and how these practices support student recruitment in the digital era while still aligning with Islamic ethical principles. The research method used was a qualitative case study, where data were collected through in-depth interviews, focus group discussions (FGDs), observation, and document analysis. The results indicate that Islamic boarding schools utilize a combination of public relations, personal selling, advertising, sales promotions, and a growing digital marketing strategy. Community engagement and interpersonal trust remain central elements, while digital platforms serve as supporting tools to expand reach and strengthen the institution's image. However, optimization of digital strategies remains hampered by limited human resources and technical capacity. This study contributes to the educational marketing literature by demonstrating how the promotional mix framework is adapted in faith-based institutions, where promotional activities are framed as community service rather than purely commercial. Practically, this study offers guidance for Islamic boarding school (pesantren) administrators to strengthen student recruitment without compromising moral integrity in communication practices.